Functional similarity analysis highlights ecosystem impacts and restoration needs. Issue 2 (19th January 2018) - Pakeman, Robin J.; Lewis, Rob J.
Abstract: Aims: To test a recently developed method of assessing functional β‐diversity – as the difference in location of the convex hull in trait space – as a means of assessing the impact of species loss and colonization over time on functional composition. This approach was tested using data from a survey and subsequent resurvey of Scottish coastal vegetation. Location: Scotland, UK. Results: Fixed dunes, slacks, unimproved grassland and mires showed the highest functional overlap through time (high correspondence in convex hull position between two surveys), while salt marsh, improved grassland and heath showed the lowest. Fixed dune was the most stable in terms of retaining the highest proportion of the original convex hull, while salt marsh was least stable. Salt marsh also showed the highest new functional space occupied, whilst mires and slacks showed the least colonization by functionally distinct species. Generally sites on the west coast of Scotland were most stable, while those on the east showed the greatest functional changes. Assessing functional β‐diversity provided a different picture to assessing species β‐diversity; high species turnover might have little impact on the functional characteristics of the vegetation, whereas the invasion of one functionally different species can have a sizeable impact on ecosystem processes. Conclusions: The method proved effective in highlighting habitats and sites where species changes had the largest impact on the functional space occupied by the plant assemblage. The method provides complementary information to that derived from other types of analysis, including about the potential needs for improved management or full‐scale restoration. Abstract : Analysing the shift in trait space (Functional Richness) occupied by a community can highlight where management should focus on the control of functionally distinct invasive species or on restoration. The technique was trialled with data from Scottish coastal vegetation; fixed dunes were most stable functionally, whilst salt marsh and improved grassland were the least stable.